HEMORRHAGIC GASTROENTERITIS IN DOG - Anna Zukiaturrahmah; Ario Ridho Gelagar; Usma Aulia; Juliadi Ramadhan (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Haemorrhagic gastroenteritis is a life-threatening disease of dogs. Gastroenteritis is inflammation of the surface of the stomach and intestines which usually occurs due to infection with microorganisms or due to consuming toxic chemicals or certain drugs. This case report aims to determine the etiology, clinical symptoms, diagnosis, prognosis and treatment of Hemorrhagic gastroenteritis disease in dogs. The examination method that is carried out is physical examination and investigations, native stool test, haematology, blood chemistry, X-ray and ultrasound. Based on the anamnesis, it was found that the dog experienced vomiting and bloody diarrhoea. Next, the native feces were examined for the presence of amoeba and bacteria, and there were no parasites. Hematologic results show leucocytosis, neutrophilia, anemia and thrombocytopenia. Blood chemistry examination results showed increased Urea, AST and ALP, and decreased albumin. Xray examination results showed presence of gas in the intestine. The results of the ultrasound examination showed that Bruno's dog's intestines had a hyperechoic appearance. The diagnosis of this case is Haemorrhagic gastroenteritis. Treatment in this case is antibiotics, probiotics, supplements, Vitamin-K, and fluid therapy. On the seventh day the animal is allowed to be taken home. The conclusion of the dog in this case was diagnosed with haemorrhagic gastroenteritis seen from the results of physical examination, supporting examinations in the form of native feces, CBC, blood chemistry, X-Ray and USG. The actions taken were administration of antibiotics, prebiotics, supplements, vit-K, and fluid therapy. It is recommended to improve sanitation of dog eating & drinking equipment and the surrounding environment. Preventive measures can be taken with complete vaccination which can be started in dogs aged six weeks.